Governance Structures: Comparing Presidential and Parliamentary Systems on Accountability, Efficiency, and Economic Outcomes - Mahmuluddin (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This study provides a comparative evaluation of two dominant governance structures—presidential and parliamentary systems—focusing on their institutional efficiency, accountability, and economic outcomes. Through a review of existing literature and case studies, the research identifies key distinctions between these systems. Presidential systems, characterized by strong centralized executive authority, often struggle with transparency and accountability, leading to bureaucratic inefficiencies. In contrast, parliamentary systems typically foster greater decentralization and consultation, promoting higher levels of accountability and transparency. Economically, countries under presidential governance tend to experience slower GDP growth, higher inflation, and increased income inequality, with growth rates averaging 0.6 to 1.2 percentage points lower than those under parliamentary governance. This is partly attributed to policies that often favor elite interests. Using a qualitative comparative approach, the study analyzes a range of case studies and policy outcomes, concluding that parliamentary systems, despite some challenges, offer superior institutional efficiency, greater accountability, and better economic performance. As a result, parliamentary systems are suggested to be a more favorable governance model in terms of transparency, decentralized governance, and economic outcomes.